Critical Discourse Analysis of Peanuts Comic Strips Loaded in The Jakarta Post - Armeria Wijaya (Tell : Teaching of English Language and Literature Journal, 2013)
This study is conducted by analyzing the intended meanings lies behind the utterances in the dialogues of Peanuts Comic Strips in the Jakarta Post. Particularly, this study is aimed at analyzing the general socio-cultural knowledge applied to find the intended meanings, the kind of visual images used by the author to transmit the message, and the goals of the comic strips being loaded in the newspapers. Qualitative approach and content analysis is applied to get descriptive information. Specifically, this study uses Critical Discourse Analysis as the research technique. It sees the goal of the comic strips being loaded in the newspaper from the similarity of the storylines and the ideologies shared with the certain news.